2019
DOI: 10.1371/journal.pone.0213876
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle yielding probability estimation model at unsignalized midblock crosswalks in Shanghai, China

Abstract: The vehicle-pedestrian encounter at midblock crosswalks in urban centers is inevitable but the challenge to urban transportation planners is in achieving a balance between traffic flow efficiency and pedestrian safety. Vehicles are expected to yield to pedestrians who have a right of way at the midblock unsignalized crosswalks but, failure to yield causes conflicts that at times are fatal. This study investigated the effect of macroscopic factors on the vehicle yielding. Six environmental factors are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Thus, multivariate normality is assumed (Kline, 1998). The tolerance factor and variance inflation factor (VIF) are used to predict multicollinearity (Malenje et al. , 2019), with a tolerance value lower than 0.1 and a VIF exceeding 10 indicating multicollinearity (Marquardt, 1980).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, multivariate normality is assumed (Kline, 1998). The tolerance factor and variance inflation factor (VIF) are used to predict multicollinearity (Malenje et al. , 2019), with a tolerance value lower than 0.1 and a VIF exceeding 10 indicating multicollinearity (Marquardt, 1980).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Thus, multivariate normality is assumed (Kline, 1998). The tolerance factor and variance inflation factor (VIF) are used to predict multicollinearity (Malenje et al, 2019), with a tolerance value lower than 0.1 and a VIF exceeding 10 indicating multicollinearity (Marquardt, 1980). In this study, the tolerance factors of the variables are all greater than 0.1 (0.320-0.654) and the VIFs are all lower than 10 (1.529-3.127), indicating no notable multivariate collinearity among the predictor variables.…”
Section: Multivariate Normal Distribution and Multicollinearity Testmentioning
confidence: 99%
“…Malenje et al [17] investigated the effects of the macroscopic factors on the vehicle yielding maneuvers at unsignalized midblock crosswalks. The results showed that the gap size and number of traffic lanes highly influenced the yielding decisions of drivers, and they were more likely to yield if e-police were present.…”
Section: Vehicle Yielding Maneuvermentioning
confidence: 99%
“…Some studies have found that willingness to yield increases when pedestrians wait near the roadway or have already stepped out into the road carriageway ( 4 , 5 , 19 ). The possibility of yielding is even greater if they are crossing the centerline lane in multi-lane crossings rather than near curbside lanes ( 6 ) or are waiting at the median ( 20 ). One of the reasons is that pedestrians are more visible to the drivers and in a vulnerable position when they are far from the curb.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fast walking or darting into traffic are also found to encourage drivers to slow down or stop for pedestrians (4,11). In addition, drivers are more likely to yield if there are many pedestrians at the crossing (19)(20)(21)(22). Large pedestrian groups not only increase pedestrian flows but tend to show more aggressive behavior because of a belief in safety in numbers.…”
Section: Pedestrian Assertiveness and Visibility To The Driversmentioning
confidence: 99%